RNA drug discovery: Conformational restriction enhances specific modulation of the T-box riboswitch function. Issue 20 (15th October 2020) - Armstrong, Ian; Aldhumani, Ali H.; Schopis, Jia L.; Fang, Fang; Parsons, Eric; Zeng, Chunxi; Hossain, Md. Ismail; Bergmeier, Stephen C.; Hines, Jennifer V.
Graphical abstract: Abstract: Antibacterial drug resistance is a global health concern that requires multiple solution approaches including development of new antibacterial compounds acting at novel targets. Targeting regulatory RNA is an emerging area of drug discovery. The T-box riboswitch is a regulatory RNA mechanism that controls gene expression in Gram-positive bacteria and is an exceptional, novel target for antibacterial drug design. We report the design, synthesis and activity of a series of conformationally restricted oxazolidinone-triazole compounds targeting the highly conserved antiterminator RNA element of the T-box riboswitch. Computational binding energies correlated with experimentally-derived Kd values indicating the predictive capabilities for docking studies within this series of compounds. The conformationally restricted compounds specifically inhibited T-box riboswitch function and not overall transcription. Complex disruption, computational docking and RNA binding specificity data indicate that inhibition may result from ligand binding to an allosteric site. These results highlight the importance of both ligand affinity and RNA conformational outcome for targeted RNA drug design.